State-of-the-art review and update of in vivo models of necrotizing enterocolitis - Bautista, Geoanna M.; Cera, Anjali J.; Chaaban, Hala; McElroy, Steven J. (Frontiers in Pediatrics, 2023)
NEC remains one of the most common causes of mortality and morbidity in preterm infants. Animal models of necrotizing enterocolitis (NEC) have been crucial in improving our understanding of this devastating disease and identifying biochemical pathways with therapeutic potential. The pathogenesis of NEC remains incompletely understood, with no specific entity that unifies all infants that develop NEC. Therefore, investigators rely on animal models to manipulate variables and provide a means to test interventions, making them valuable tools to enhance our understanding and prevent and treat NEC. The advancements in molecular analytic tools, genetic manipulation, and imaging modalities and the emergence of scientific collaborations have given rise to unique perspectives and disease correlates, creating novel pathways of investigation. A critical review and understanding of the current phenotypic considerations of the highly relevant animal models of NEC are crucial to developing novel therapeutic and preventative strategies for NEC.